(untitled) (Web of Teachers: Inderscience Research, 2025)
Aesthetic education in early childhood is essential for fostering creativity, emotional intelligence, and artistic expression. Modern pedagogical technologies provide innovative tools and methods that enhance this process, making learning more engaging and interactive. This paper examines contemporary digital resources, including multimedia applications, virtual simulations, and interactive storytelling, alongside traditional artistic approaches such as music, painting, and drama. By integrating technology with age-appropriate teaching strategies, educators can create dynamic learning environments that support children’s aesthetic appreciation and creative skills. The study explores effective methodologies and the impact of modern technological tools on preschoolers’ aesthetic development.